Bi-based glass encapsulating material for ceramic USB connector and manufacturing method thereof and ceramic USB connector using the same

KR1020260131324APending Publication Date: 2026-09-01KOREA INST OF CERAMIC ENG & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020250023450
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2026-09-01

Smart Images

  • Figure PAT00019_ABST
    Figure PAT00019_ABST
Patent Text Reader

Abstract

A Bi-based glass encapsulant for a ceramic USB connector, a method for manufacturing the same, and a ceramic USB connector using the same are disclosed, wherein a low glass transition temperature and an appropriate coefficient of thermal expansion are secured by optimizing the composition and composition ratio of the Bi-based glass, and excellent thermal properties are secured to improve electrical properties. The Bi-based glass encapsulant for a ceramic USB connector according to the present invention is a BiSB-based glass encapsulant comprising Bi2O3, SiO2, and B2O3, or a BiSZ-based glass encapsulant comprising Bi2O3, SiO2, and ZnO, wherein the BiSB-based glass encapsulant comprises SiO2 20 to 60 mol%, Bi2O3 10 to 50 mol%, and B2O3 5 to 55 mol%, and the BiSZ-based glass encapsulant comprises SiO2 20 to 60 mol%, Bi2O3 10 to 50 mol%, and ZnO 5 to 35 mol%.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a Bi-based glass encapsulant for ceramic USB connectors, a method for manufacturing the same, and a ceramic USB connector using the same. More specifically, the invention relates to a Bi-based glass encapsulant for ceramic USB connectors, a method for manufacturing the same, and a ceramic USB connector using the same, wherein excellent thermal characteristics are secured and electrical characteristics are improved by optimizing the composition and composition ratio of the Bi-based glass to secure a low glass transition temperature and an appropriate coefficient of thermal expansion. Background Technology

[0003] Generally, communication between electronic devices transmits electromagnetic signals through the connection of electrical connectors, such as the relatively frequently used Universal Serial Bus (USB).

[0004] USB Type-C connectors are primarily used for such electrical connectors. These USB Type-C connectors offer the advantage of enabling both forward and reverse insertion connections. The trend in the mobile phone industry is to replace existing Micro USB interfaces with USB Type-C interfaces, thereby establishing USB Type-C as the industry standard interface.

[0005] However, until now, most USB Type-C connectors have been manufactured using plastic (LCP)-based connectors, which has the following problems.

[0006] First, plastic (LCP)-based connectors suffer from problems such as attenuation and delay of high-frequency signals due to the high dielectric loss of the plastic material.

[0007] Second, due to the low hardness of plastic (LCP)-based connectors, physical damage occurs from contact during the process of repeated insertion.

[0008] Third, plastic (LCP)-based connectors are hindering the development of USB 4.0 due to the low heat resistance inherent to plastic, which leads to ignition caused by foreign substances and thermal deformation from prolonged use.

[0009] Fourth, plastic (LCP)-based connectors are exposed to new standard limits, such as frequency characteristics and heat dissipation during power transmission.

[0010] A relevant prior art document is Korean Patent Publication No. 10-2007-0119812 (published Dec. 21, 2007), which describes a smokeless encapsulating material composition for a surface light source and an encapsulating method using the same. The problem to be solved

[0012] The objective of the present invention is to provide a Bi-based glass encapsulant for a ceramic USB connector, a method for manufacturing the same, and a ceramic USB connector using the same, which secures a low glass transition temperature and an appropriate coefficient of thermal expansion by optimizing the composition and composition ratio of the Bi-based glass, as well as secures excellent thermal properties to improve electrical properties. means of solving the problem

[0014] A Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention for achieving the above objective is a BiSB-based glass encapsulant comprising Bi2O3, SiO2, and B2O3, or a BiSZ-based glass encapsulant comprising Bi2O3, SiO2, and ZnO, wherein the BiSB-based glass encapsulant comprises SiO2 20 to 60 mol%, Bi2O3 10 to 50 mol%, and B2O3 5 to 55 mol%, and the BiSZ-based glass encapsulant comprises SiO2 20 to 60 mol%, Bi2O3 10 to 50 mol%, and ZnO 5 to 35 mol%.

[0015] It is more preferable that the above SiO2 contains 25 to 50 mol%.

[0016] It is more preferable that the above Bi2O3 contains 20 to 40 mol%.

[0017] It is more preferable that the above B2O3 contains 10 to 50 mol%.

[0018] It is more preferable that the above ZnO contains 10 to 30 mol%.

[0019] The above Bi-based glass encapsulant for the ceramic USB connector is 7.3 × 10 -6 / ℃ ~ 10.33 × 10 -6 It has a coefficient of thermal expansion of / ℃.

[0020] The Bi-based glass encapsulant for the ceramic USB connector above has a glass transition temperature of 480°C or lower.

[0021] The Bi-based glass encapsulant for the ceramic USB connector above has a dielectric constant of 15 or less.

[0023] A method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention for achieving the above objective comprises: (a) a step of coarsely grinding BiSB-based glass containing SiO220 to 60 mol%, Bi2O310 to 50 mol%, and B2O35 to 55 mol%, or BiSZ-based glass containing SiO220 to 60 mol%, Bi2O310 to 50 mol%, and ZnO 5 to 35 mol%; (b) a step of finely grinding the coarsely ground glass powder; (c) a step of mixing a binder with the finely ground glass powder and then molding it; and (d) a step of sintering the molded product.

[0024] In step (a) above, the SiO2 contains 25 to 50 mol%.

[0025] In step (a) above, the Bi2O3 contains 20 to 40 mol%.

[0026] In step (a) above, the B2O3 contains 10 to 50 mol%.

[0027] In step (a) above, the ZnO contains 10 to 30 mol%.

[0028] In step (c) above, the molding is performed for 1 to 10 minutes at a pressure of 1 to 10 ton / ㎠.

[0029] In step (d) above, the sintering is carried out at 450 to 600°C for 1 to 12 hours.

[0030] After step (d) above, the Bi-based glass encapsulant for the ceramic USB connector is 7.3 × 10 -6 / ℃ ~ 10.33 × 10 -6 It has a coefficient of thermal expansion of / ℃.

[0031] After step (d) above, the Bi-based glass encapsulant for the ceramic USB connector has a glass transition temperature of 480°C or lower.

[0032] After step (d) above, the Bi-based glass encapsulant for the ceramic USB connector has a dielectric constant of 15 or less.

[0034] A ceramic USB connector using a Bi-based glass encapsulant composition according to an embodiment of the present invention for achieving the above objective is a ceramic USB connector using a Bi-based glass encapsulant, wherein the Bi-based glass encapsulant is 7.3 × 10 -6 / ℃ ~ 10.33 × 10 -6 It is characterized by having a coefficient of thermal expansion of / ℃, a glass transition temperature of 480℃ or less, and a dielectric constant of 15 or less. Effects of the invention

[0036] The Bi-based glass encapsulant for a ceramic USB connector according to the present invention, the method for manufacturing the same, and the ceramic USB connector using the same can improve electrical characteristics by securing a low glass transition temperature and an appropriate coefficient of thermal expansion, as well as excellent thermal characteristics, through optimizing the composition and composition ratio of the Bi-based glass.

[0037] As a result, the Bi-based glass encapsulant for a ceramic USB connector according to the present invention, the method for manufacturing the same, and the ceramic USB connector using the same have 7.3 × 10 -6 / ℃ ~ 10.33 × 10 -6 By having a coefficient of thermal expansion of / °C, a low glass transition temperature of 480°C or less, and a low dielectric constant of 15 or less, it is possible to prevent problems such as attenuation and delay of high-frequency signals caused by high dielectric loss of conventional plastic (LCP)-based connectors.

[0038] Accordingly, the Bi-based glass encapsulant for a ceramic USB connector according to the present invention, the method for manufacturing the same, and the ceramic USB connector using the same enable power transmission of 100W or more and dustproof and waterproof design by sealing the ceramic core of the ceramic USB connector with a Bi-based glass encapsulant made of Bi-based glass material.

[0039] Thus, the Bi-based glass encapsulant for a ceramic USB connector and the method for manufacturing the same according to the present invention, and the ceramic USB connector using the same, are composed of a Bi-based glass composition and have 7.3 × 10 -6 / ℃ ~ 10.33 × 10 -6 By having a coefficient of thermal expansion of / °C and a low dielectric constant of 15 or less, problems such as attenuation and delay of high-frequency signals caused by high dielectric loss of conventional plastic (LCP)-based connectors can be prevented in advance.

[0040] In addition, the Bi-based glass encapsulant for a ceramic USB connector according to the present invention, the method for manufacturing the same, and the ceramic USB connector using the same are composed of a Bi-based glass composition and have high hardness, thereby minimizing physical damage caused by contact during the process of repeatedly inserting the connector.

[0041] Furthermore, the Bi-based glass encapsulant for a ceramic USB connector according to the present invention, the method for manufacturing the same, and the ceramic USB connector using the same are composed of a Bi-based glass composition, which enables excellent heat resistance; thus, ignition caused by foreign substances and thermal deformation due to prolonged use do not occur, which are inherently low heat resistances of conventional plastics. Brief explanation of the drawing

[0043] FIG. 1 is a process flowchart showing a method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention. FIGS. 2 to 5 are photographs showing samples prepared according to Examples 1 to 10. Figure 6 is a graph showing the Tg and CTE measurement results for samples prepared according to Examples 1 to 6. Figure 7 is a graph showing the Tg and CTE measurement results for samples prepared according to Examples 7 to 9. FIGS. 8 to 11 are SEM images showing the microstructure of samples prepared according to Examples 3 to 6 after calcination. Figure 12 is an SEM image showing the microstructure of the sample prepared according to Example 9 after calcination. FIG. 13 is a graph showing the results of measuring the shrinkage rate and dielectric constant for samples prepared according to Examples 3 to 6 and 9. FIG. 14 is a graph showing the results of measuring shrinkage rate and dielectric strength for samples prepared according to Examples 3 to 6 and 9. FIG. 15 is a graph showing the results of measuring the dielectric constant and breakdown voltage for samples prepared according to Examples 3 to 6 and 9. FIG. 16 is a photograph showing a ceramic USB connector manufactured using a sample according to Example 4. Specific details for implementing the invention

[0044] The advantages and features of the present invention and the methods for achieving them will become clear by referring to the embodiments described below in detail together with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below but may be implemented in various different forms. These embodiments are provided merely to ensure that the disclosure of the present invention is complete and to fully inform those skilled in the art of the scope of the invention, and the present invention is defined only by the scope of the claims. Throughout the specification, the same reference numerals refer to the same components.

[0045] The Bi-based glass encapsulant for a ceramic USB connector according to a preferred embodiment of the present invention, the method for manufacturing the same, and the ceramic USB connector using the same will be described in detail below with reference to the attached drawings.

[0047] The Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention enables power transmission of 100W or more and dustproof and waterproof design by sealing the ceramic core of the ceramic USB connector with a Bi-based glass encapsulant made of Bi-based glass material.

[0048] Thus, the Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention is composed of a Bi-based glass composition of 7.3 × 10 -6 / ℃ ~ 10.33 × 10 -6 By having a coefficient of thermal expansion of / °C and a low dielectric constant of 15 or less, it is possible to prevent problems such as attenuation and delay of high-frequency signals caused by the high dielectric loss of conventional plastic (LCP)-based connectors.

[0049] In addition, the Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention is composed of a Bi-based glass composition and has high hardness, thereby minimizing physical damage caused by contact during the process of repeatedly inserting the connector.

[0050] In addition, the Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention is composed of a Bi-based glass composition, which enables excellent heat resistance; thus, ignition caused by foreign substances and thermal deformation due to prolonged use do not occur, which are inherently low heat resistances of conventional plastics.

[0051] As a result, a ceramic USB connector manufactured using a Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention can enable high-speed data transmission suitable for frequency characteristics of 40 GHz or higher at a transmission speed of 20 Gbps or more.

[0052] In addition, the ceramic USB connector manufactured using the Bi-based glass encapsulant for the ceramic USB connector according to the embodiment of the present invention can not only achieve an excellent heat dissipation effect for transmission of 100W or more, but also ensure reliability by having a compressive strength more than 20 times higher than that of existing plastic-based connectors.

[0054] To this end, the Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention comprises a BiSB-based glass encapsulant comprising Bi2O3, SiO2, and B2O3, or a BiSZ-based glass encapsulant comprising Bi2O3, SiO2, and ZnO.

[0055] More specifically, the BiSB-based glass encapsulant comprises SiO220 to 60 mol%, Bi2O310 to 50 mol%, and B2O35 to 55 mol%, and the BiSZ-based glass encapsulant comprises SiO220 to 60 mol%, Bi2O310 to 50 mol%, and ZnO5 to 35 mol%.

[0056] SiO2 is a glass-forming oxide and serves as a component for establishing the glass framework. Furthermore, SiO2 is an effective component for improving glass viscosity, as its content allows for easy control of glass viscosity.

[0057] The content of such SiO2 is preferably in the range of 20 to 60 mol%, and more preferably in the range of 25 to 50 mol%. If the SiO2 content is too low, less than 20 mol%, the internal permeability may deteriorate. Conversely, if the SiO2 content is too high, exceeding 60 mol%, the glass transition temperature (Tg) or the viscosity of the glass is prone to increase, and undissolved substances are prone to occur.

[0058] Bi2O3 is a component that lowers the melting point of glass, thereby lowering the glass transition temperature (Tg). It is preferable that the content of Bi2O3 be in the range of 10 to 50 mol%, and more preferable that it be in the range of 20 to 40 mol%. If the content of Bi2O3 is too low, less than 10 mol%, it is difficult to properly exhibit the above effect. Conversely, if the content of Bi2O3 is too high, exceeding 50 mol%, it is undesirable because it can act as a factor that increases the dielectric constant.

[0059] B2O3 is a representative network-forming oxide and, together with SiO2, is a key component that enables sufficient vitrification. In addition, B2O3 plays a role in lowering the glass transition temperature (Tg) and the softening temperature. Considering this, the content of B2O3 is preferably 5 to 55 mol%, and more preferably 10 to 50 mol%.

[0060] ZnO is a component that performs both the roles of a network-forming agent and a network-modifying agent in terms of the structural aspects of the glass. In addition, ZnO lowers the glass transition temperature without increasing the coefficient of thermal expansion. Considering this, it is preferable that the ZnO content be 5 to 35 mol%, and more preferable that it be 10 to 30 mol%.

[0062] The Bi-based glass encapsulant for a ceramic USB connector according to the embodiment of the present invention described above can improve electrical characteristics by securing excellent thermal properties in addition to securing a low glass transition temperature and an appropriate coefficient of thermal expansion through optimizing the composition and composition ratio of the Bi-based glass.

[0063] As a result, the Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention is 7.3 × 10 -6 / ℃ ~ 10.33 × 10 -6 By having a coefficient of thermal expansion of / °C, a low glass transition temperature of 480°C or less, and a low dielectric constant of 15 or less, it is possible to prevent problems such as attenuation and delay of high-frequency signals caused by high dielectric loss of conventional plastic (LCP)-based connectors.

[0064] More specifically, the Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention is 7.3 × 10 -6 / ℃ ~ 10.33 × 10 -6 It has a coefficient of thermal expansion of / °C, a low glass transition temperature of 430 to 475°C, and a low dielectric constant of 10 to 14.5.

[0065] Accordingly, the Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention enables power transmission of 100W or more and dustproof and waterproof design by sealing the ceramic core of the ceramic USB connector with a Bi-based glass encapsulant made of Bi-based glass material.

[0066] Thus, the Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention is composed of a Bi-based glass composition of 7.3 × 10 -6 / ℃ ~ 10.33 × 10 -6 By having a coefficient of thermal expansion of / °C and a low dielectric constant of 15 or less, problems such as attenuation and delay of high-frequency signals caused by high dielectric loss of conventional plastic (LCP)-based connectors can be prevented in advance.

[0067] In addition, the Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention is composed of a Bi-based glass composition and has high hardness, thereby minimizing physical damage caused by contact during the process of repeatedly inserting the connector.

[0068] In addition, the Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention is composed of a Bi-based glass composition, which enables excellent heat resistance; thus, ignition caused by foreign substances and thermal deformation due to prolonged use do not occur due to the inherently low heat resistance of plastic.

[0069] As a result, a ceramic USB connector manufactured using a Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention can enable high-speed data transmission suitable for frequency characteristics of 40 GHz or higher at a transmission speed of 20 Gbps or more.

[0070] In addition, the ceramic USB connector manufactured using the Bi-based glass encapsulant for the ceramic USB connector according to the embodiment of the present invention can not only provide excellent heat dissipation effects for transmission of 100W or more, but also ensure reliability by having a compressive strength more than 20 times higher than that of existing plastic-based connectors.

[0072] Hereinafter, a method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention will be described with reference to the attached drawings.

[0073] FIG. 1 is a process flowchart showing a method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention.

[0074] As illustrated in FIG. 1, a method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention includes a coarse grinding step (S110), a fine grinding step (S120), a molding step (S130), and a sintering step (S140).

[0076] coarse crushing

[0077] In the coarse grinding step (S110), BiSB-based glass containing SiO220 to 60 mol%, Bi2O310 to 50 mol%, and B2O35 to 55 mol%, or BiSZ-based glass containing SiO220 to 60 mol%, Bi2O310 to 50 mol%, and ZnO5 to 35 mol% is coarsely ground.

[0078] Here, it is more preferable that SiO2 contains 25 to 50 mol%, and Bi2O3 contains 20 to 40 mol%.

[0079] In addition, it is more preferable to include 10 to 50 mol% of B2O3 and 10 to 30 mol% of ZnO.

[0080] In this step, for BiSB-based glass or BiSZ-based glass, each raw material is mixed in the above composition ratio, the mixed raw material is placed in a crucible, and the crucible containing the mixed raw material is charged into a melting furnace to melt the mixed raw material.

[0081] At this time, it is preferable to perform the melting at 1,000 to 1,300°C for 10 minutes to 12 hours. If the melting temperature is below 1,000°C, the mixed raw materials may not melt completely, and if the melting temperature exceeds 1,300°C, excessive energy consumption is required, making it uneconomical.

[0082] In addition, if the melting time is too short, such as less than 10 minutes, the mixed raw materials may not be sufficiently melted, and if the melting time is too long, such as exceeding 24 hours, excessive energy consumption is required, making it uneconomical.

[0083] Here, it is preferable that the heating rate of the melting furnace be 5 to 50℃ / min. If the heating rate of the melting furnace is too slow at less than 5℃ / min, it takes too long and productivity decreases, and if the heating rate of the melting furnace is too fast at more than 50℃ / min, the amount of volatilization of the mixed raw materials increases due to the rapid rise in temperature, which may result in poor glass properties, so it is not desirable.

[0084] It is preferable to perform this melting in an oxidizing atmosphere such as oxygen (O2) or air.

[0085] Next, the molten material melted in the furnace is cooled to manufacture glass.

[0086] In this step, coarse grinding may be performed physically using a mortar and pestle, but is not limited thereto.

[0088] fine grind

[0089] In the fine grinding step (S120), the coarsely ground glass powder is finely ground.

[0090] Here, fine grinding may be performed using at least one selected from ball milling, V-mixer, 3D tumbling mixer, attrition milling, etc. Among these, it is more preferable to use ball milling for fine grinding.

[0091] To examine this ball milling process in detail, coarsely ground glass powder is loaded into a ball milling machine, and the glass powder is mechanically and uniformly ground by rotating the ball milling machine at a constant speed. The balls used in ball milling may be made of ceramics such as zirconia or alumina, and the balls may all be of the same size or may use balls of two or more different sizes together. Uniform grinding is achieved by adjusting the size of the balls, the milling time, and the rotational speed per minute of the ball milling machine.

[0092] For example, considering the particle size of the glass powder, the size of the ball can be set to a range of 1 to 30 mm, and the rotational speed of the ball milling machine can be set to a range of 50 to 500 rpm. It is preferable to perform ball milling for 10 minutes to 24 hours. Through ball milling, the glass powder is ground into fine particles and has a uniform particle size distribution. In this way, it is preferable that the glass powder produced has an average diameter of 1 to 10 μm.

[0094] plastic surgery

[0095] In the molding step (S130), a binder is mixed with finely ground glass powder and then molded.

[0096] Here, it is preferable to perform press forming at a pressure of 1 to 10 ton / ㎠ for 1 to 10 minutes. If the press forming pressure is less than 1 ton / ㎠ or the press forming time is less than 1 minute, it may be difficult to secure the mechanical strength of the molded product. Conversely, if the press forming pressure exceeds 10 ton / ㎠ or the press forming time exceeds 10 minutes, it is not desirable as there is a risk of damage to the molded product due to excessive pressure.

[0098] Sintering

[0099] In the sintering step (S140), the molded product is sintered to form a Bi-based glass encapsulant for a ceramic USB connector.

[0100] In this step, it is preferable to perform sintering at 450 to 600°C for 1 to 12 hours. If the sintering temperature is too low, below 450°C, or the sintering time is less than 1 hour, mechanical properties may be poor due to incomplete firing. Conversely, if the sintering temperature exceeds 600°C or the sintering time exceeds 12 hours, energy consumption is high, making it uneconomical. This sintering may be performed in an oxidizing atmosphere such as oxygen (O2) or air, but is not limited thereto.

[0101] After the sintering step (S140), the Bi-based glass encapsulant for the ceramic USB connector is 7.3 × 10 -6 / ℃ ~ 10.33 × 10 -6 It has a coefficient of thermal expansion of / ℃, a low glass transition temperature of 480℃ or less, and a low dielectric constant of 15 or less.

[0102] With this, the method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention may be concluded.

[0104] As described above, the method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention enables the improvement of electrical properties by securing excellent thermal properties, in addition to securing a low glass transition temperature and an appropriate coefficient of thermal expansion, through optimizing the composition and composition ratio of the Bi-based glass.

[0105] As a result, the method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention is 7.3 × 10 -6 / ℃ ~ 10.33 × 10 -6By having a coefficient of thermal expansion of / °C, a low glass transition temperature of 480°C or less, and a low dielectric constant of 15 or less, it is possible to prevent problems such as attenuation and delay of high-frequency signals caused by high dielectric loss of conventional plastic (LCP)-based connectors.

[0106] Accordingly, the method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention enables power transmission of 100W or more and dustproof and waterproof design by sealing the ceramic core of the ceramic USB connector with a Bi-based glass encapsulant made of Bi-based glass material.

[0107] Thus, the method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention is composed of a Bi-based glass composition of 7.3 × 10 -6 / ℃ ~ 10.33 × 10 -6 By having a coefficient of thermal expansion of / °C and a low dielectric constant of 15 or less, problems such as attenuation and delay of high-frequency signals caused by high dielectric loss of conventional plastic (LCP)-based connectors can be prevented in advance.

[0108] In addition, the method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention is composed of a Bi-based glass composition and has high hardness, thereby minimizing physical damage caused by contact during the process of repeatedly inserting the connector.

[0109] In addition, the method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector according to an embodiment of the present invention is composed of a Bi-based glass composition, which enables excellent heat resistance; therefore, ignition caused by foreign substances and thermal deformation due to prolonged use do not occur, which are inherently low heat resistances of conventional plastics.

[0111] Examples

[0112] Hereinafter, the structure and operation of the present invention will be explained in more detail through preferred embodiments of the present invention. However, these are presented as preferred examples of the present invention and should not be interpreted in any way as limiting the present invention.

[0113] Details not listed here can be sufficiently technically inferred by a person skilled in this field, so their explanation will be omitted.

[0115] 1. Sample Preparation

[0116] Glass samples according to Examples 1 to 10 and Comparative Example 1 were prepared with the compositions and composition ratios listed in Tables 1 and 2. At this time, the glass composition was prepared by batch combining reagents of Bi2O3, SiO2, B2O3, and ZnO. The batch mixture was placed in an alumina crucible to melt it and melted twice at 1,100°C for 1 hour, after which the molten material was poured into a graphite mold and cooled to room temperature.

[0118] [Table 1]

[0119]

[0121] [Table 2]

[0122]

[0124] 2. Evaluation of Thermal Properties

[0125] Table 3 shows the results of the physical property evaluation for samples prepared according to Examples 1 to 10 and Comparative Example 1. Additionally, Figures 2 to 5 are photographs showing samples prepared according to Examples 1 to 10. In this case, Figures 2 (a) to (c) show samples according to Examples 1 to 3, Figures 3 (a) to (c) show samples according to Examples 4 to 6, Figures 4 (a) and (b) show samples according to Examples 7 to 8, and Figures 5 (a) and (b) show samples according to Examples 9 to 10. Furthermore, Figure 6 is a graph showing the Tg and CTE measurement results for samples prepared according to Examples 1 to 6, and Figure 7 is a graph showing the Tg and CTE measurement results for samples prepared according to Examples 7 to 9.

[0127] 1) Evaluation of thermal properties

[0128] Thermal properties were evaluated using a thermomechanical analyzer. The thermal property evaluation items were the coefficient of thermal expansion and the glass transition temperature.

[0129] The coefficient of thermal expansion is a result indicating the degree of expansion of a material in the temperature range of 100℃ to 300℃, and the glass transition temperature (T), which is a thermal characteristic g ) indicates the temperature range at which glass transition occurs. Measurements were taken using a TMA (Q400-EM, TA instruments, USA) at a heating rate of 5℃ / min.

[0131] [Table 3]

[0132]

[0133] As shown in Tables 1 to 3 and FIGS. 2 to 7, among the samples according to Examples 1 to 6 corresponding to BiSBx glass, the samples according to Examples 1 to 5, excluding the sample according to Example 6 (BiSB60), have a glass transition temperature (T g It was confirmed that both the coefficient of thermal expansion (CTE) and the coefficient of thermal expansion (CTE) satisfied the target values.

[0134] In particular, in the case of the sample according to Example 2 (BiSB10), compared to the sample according to Comparative Example 1 (BiS), which is the basic composition, T g It was confirmed that the temperature increased by 48℃ and the CTE increased by 0.13.

[0135] However, as shown in Table 3 and Figure 6, as the amount of B2O3 added increases, T g It was confirmed that [value] tended to increase and CTE tended to decrease.

[0137] Meanwhile, as shown in Tables 1 to 3 and FIGS. 2 to 7, the samples according to Examples 7 to 9 corresponding to BiSZx glass have a glass transition temperature (T g It was confirmed that both the coefficient of thermal expansion (CTE) and the coefficient of thermal expansion (CTE) satisfied the target values.

[0138] In particular, in the case of the sample according to Example 7 (BiSZ10), compared to the sample according to Comparative Example 1 (BiS), which is the basic composition, T g It was confirmed that [the value] decreased by 36℃ and CTE increased by 0.83.

[0139] However, as shown in Table 3 and Figure 7, as the amount of ZnO added increases, T g It was confirmed that it increased, while CTE showed a similar trend without significant change.

[0141] 3. Evaluation of Electrical Characteristics

[0142] Table 4 shows the results of measuring the dielectric constant and dielectric strength for samples prepared according to Examples 3 to 6 and 9. Additionally, Figures 8 to 11 are SEM images showing the microstructure after calcination of samples prepared according to Examples 3 to 6, and Figure 12 is an SEM image showing the microstructure after calcination of a sample prepared according to Example 9. Here, dielectric strength and dielectric constant were measured to evaluate the electrical properties of the samples according to Examples 3 to 6 and 9. For the evaluation of electrical properties, the samples according to Examples 3 to 6 and 9 were coarsely ground using a mortar and pestle, and then finely ground into particles with an average diameter of 5 μm by ball milling using zirconia balls for 36 hours. Subsequently, a binder was mixed with the finely ground powder, and the mixed powder was molded and sintered. At this time, the sintering temperature was set based on a shrinkage rate of 14%.

[0144] 1) Withstand voltage measurement

[0145] Electrical characteristics were evaluated using an AC withstand voltage tester. Here, withstand voltage refers to the maximum voltage that an insulator or electrical device can withstand without insulation breakdown. This withstand voltage is 100V. ac It was evaluated whether it could withstand 1 min using an AC withstand voltage test (TOS5200, Kikusui, Korea).

[0147] 2) Measurement of dielectric constant

[0148] Electrical characteristics were evaluated using an LCR meter (Inductance Capacitance Resistance Meter). Here, the dielectric constant is a relative value indicating how well a material blocks or deforms an electric field. In this case, Equation 1: ε (dielectric constant) = C p (Capacitance) The dielectric constant value was measured using × t (thickness) / {ε0 (vacuum permittivity) × A (area)}.

[0150] [Table 4]

[0151]

[0152] As shown in Table 4 and Figures 8 to 12, it was confirmed that the samples according to Examples 3 to 6 and 9 all satisfied the withstand voltage test conditions for 1 minute at 100 Vac (RMS).

[0153] In particular, it was confirmed that the sample according to Example 3 exhibited the lowest dielectric constant value, and it is believed that the reduction in the dielectric constant was influenced by the optimization of the Bi content and B content.

[0155] Meanwhile, FIG. 13 is a graph showing the results of measuring the shrinkage rate and dielectric constant for samples prepared according to Examples 3 to 6 and 9, FIG. 14 is a graph showing the results of measuring the shrinkage rate and dielectric strength for samples prepared according to Examples 3 to 6 and 9, and FIG. 15 is a graph showing the results of measuring the dielectric strength and dielectric strength for samples prepared according to Examples 3 to 6 and 9.

[0156] As shown in Table 4 and Figure 13, it was confirmed that the samples according to Examples 3 to 6 and 9 exhibited a shrinkage rate between 0.816 and 0.851.

[0157] In particular, it was confirmed that the samples according to Example 4 (BiSB40), Example 5 (BiSB50), and Example 6 (BiSB60) exhibited low dielectric constants and satisfied the target value.

[0158] In addition, as shown in Table 4 and Figure 14, it was confirmed that the samples according to Examples 3 to 6 and 9 exhibited a shrinkage rate between 0.816 and 0.851.

[0159] In particular, it was confirmed that the samples according to Example 5 (BiSB50) and Example 6 (BiSB60) exhibited low dielectric strength characteristics and satisfied the target value.

[0160] In addition, as shown in Table 4 and Figure 15, it was confirmed that the samples according to Example 4 (BiSB40), Example 5 (BiSB50), and Example 6 (BiSB60) exhibited low dielectric constant and dielectric strength.

[0162] Meanwhile, Fig. 16 is a photograph showing a ceramic USB connector manufactured using a sample according to Example 4. Here, a binder, a plasticizer, and distilled water were mixed with glass powder according to Example 4 and ball milled for 6 hours, after which glass powder was manufactured into a granule shape using a spray dryer. Subsequently, the glass powder was inserted into a mold and uniaxially pressed to produce a preform shape. Then, the glass preform was inserted between a ceramic core and a metal shell, sealed at the melting temperature of the glass, and then welded to a metal shell equipped with screw fastening holes for PC fastening to manufacture a ceramic USB connector. At this time, Fig. 16 (a) shows the glass encapsulant manufactured according to Example 4, and Fig. 16 (b) shows the ceramic USB connector manufactured according to Example 4.

[0163] As shown in FIG. 16, in the ceramic USB connector manufactured according to Example 4, it can be seen that a glass encapsulator is inserted and placed between the ceramic core and the metal shell to stably encapsulate the ceramic core.

[0164] Accordingly, the ceramic USB connector is 7.3 × 10 -6 / ℃ ~ 10.33 × 10 -6 It can be sealed by a glass encapsulant having a coefficient of thermal expansion of / °C, a glass transition temperature of 480°C or less, and a dielectric constant of 15 or less, thereby enabling transmission of 40 Gbps / 100 Watt.

[0166] Although the present invention has been described above with reference to embodiments, various changes and modifications can be made by those skilled in the art to which the present invention pertains. Such changes and modifications are considered to be within the scope of the present invention as long as they do not depart from the technical concept provided by the present invention. Accordingly, the scope of rights of the present invention should be determined by the claims set forth below. Explanation of the symbols

[0168] S110: Coarse crushing stage S120: Fine grinding step S130: Forming stage S140: Sintering step

Claims

Claim 1 A Bi-based glass encapsulant for a ceramic USB connector, comprising a BiSB-based glass encapsulant containing Bi2O3, SiO2, and B2O3, or a BiSZ-based glass encapsulant containing Bi2O3, SiO2, and ZnO, wherein the BiSB-based glass encapsulant contains SiO2 20 to 60 mol%, Bi2O3 10 to 50 mol%, and B2O3 5 to 55 mol%, and the BiSZ-based glass encapsulant contains SiO2 20 to 60 mol%, Bi2O3 10 to 50 mol%, and ZnO 5 to 35 mol%. Claim 2 Bi-based glass encapsulant for ceramic USB connectors according to claim 1, characterized in that the SiO2 comprises 25 to 50 mol%. Claim 3 A Bi-based glass encapsulant for a ceramic USB connector according to claim 1, characterized in that the Bi2O3 comprises 20 to 40 mol%. Claim 4 Bi-based glass encapsulant for ceramic USB connectors according to claim 1, characterized in that the B2O3 comprises 10 to 50 mol%. Claim 5 Bi-based glass encapsulant for ceramic USB connectors according to claim 1, characterized in that the ZnO comprises 10 to 30 mol%. Claim 6 In claim 1, the Bi-based glass encapsulant for the ceramic USB connector is 7.3 × 10 -6 / ℃ ~ 10.33 × 10 -6 Bi-based glass encapsulant for ceramic USB connectors, characterized by having a coefficient of thermal expansion of / ℃. Claim 7 A Bi-based glass encapsulant for a ceramic USB connector according to claim 1, characterized in that the Bi-based glass encapsulant for the ceramic USB connector has a glass transition temperature of 480°C or lower. Claim 8 A Bi-based glass encapsulant for a ceramic USB connector according to claim 1, characterized in that the Bi-based glass encapsulant for the ceramic USB connector has a dielectric constant of 15 or less. Claim 9 (a) a step of coarsely grinding BiSB-based glass containing SiO220 to 60 mol%, Bi2O310 to 50 mol%, and B2O35 to 55 mol%, or BiSZ-based glass containing SiO220 to 60 mol%, Bi2O310 to 50 mol%, and ZnO 5 to 35 mol%; (b) a step of finely grinding the coarsely ground glass powder; (c) a step of mixing a binder with the finely ground glass powder and then molding it; and (d) a step of sintering the molded product; characterized by comprising a method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector. Claim 10 A method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector, characterized in that, in step (a) above, the SiO2 comprises 25 to 50 mol%. Claim 11 A method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector according to claim 9, wherein in step (a) above, the Bi2O3 comprises 20 to 40 mol%. Claim 12 A method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector according to claim 9, wherein in step (a) above, the B2O3 comprises 10 to 50 mol%. Claim 13 A method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector according to claim 9, wherein in step (a) above, the ZnO comprises 10 to 30 mol%. Claim 14 A method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector, characterized in that, in step (c) above, the molding is performed for 1 to 10 minutes at a pressure of 1 to 10 ton / ㎠. Claim 15 A method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector, characterized in that, in step (d) above, the sintering is performed at 450 to 600°C for 1 to 12 hours. Claim 16 In claim 9, after step (d) above, the Bi-based glass encapsulant for the ceramic USB connector is 7.3 × 10 -6 / ℃ ~ 10.33 × 10 -6 A method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector, characterized by having a coefficient of thermal expansion of / ℃. Claim 17 A method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector according to claim 9, wherein, after step (d) above, the Bi-based glass encapsulant for a ceramic USB connector has a glass transition temperature of 480°C or lower. Claim 18 A method for manufacturing a Bi-based glass encapsulant for a ceramic USB connector according to claim 9, wherein, after step (d) above, the Bi-based glass encapsulant for a ceramic USB connector has a dielectric constant of 15 or less. Claim 19 A ceramic USB connector using a Bi-based glass encapsulant manufactured by a method according to any one of claims 9 to 18, wherein the Bi-based glass encapsulant is 7.3 × 10 -6 / ℃ ~ 10.33 × 10 -6 A ceramic USB connector using a Bi-based glass encapsulant, characterized by having a coefficient of thermal expansion of / ℃, a glass transition temperature of 480℃ or less, and a dielectric constant of 15 or less.